Learning from experience – a probe into the off-campus internships under the five-year cosmetology technical and vocational education program. Issue 2 (21st May 2020) - Ju-Hsuan, Yeh; Lo, Tsai-Yun; Wu, Ming-Chang; Wang, Li-Feng
Abstract : Purpose: This paper aims to probe into the implementation of internship courses under the five-year cosmetology program in Taiwan from the perspective of Dewey's philosophies in hopes that the analysis can serve as reference for schools in planning their internship courses in the future. Design/methodology/approach: This paper probes into the off-campus internship courses under Taiwan's five-year junior college education program by applying Dewey's empirical philosophy. Findings: The study aims to understand the learning experience acquired by students from learning by doing internship courses as reference for future internship design. The current internship courses comprise the follows: summer, during the semester and for a full academic year. The experience of summer internship is career exploration, the experience for semester internship is career experience and the experience from academic-year internship is career choice. The internship strategies are designed according to the three different internship approaches, so that the internship courses can implement the educational effect of "learning from experience". Practical implications: To minimize the discrepancy between the cosmetology program under the five-year junior college education and the employment market, credit-based off-campus internship courses are arranged for students' final years at school. Social implications: Through on-site trainings, students accumulate work experience and explore into a related career field. The accumulation of experience and gaining of insights mirror the philosophy of learning by doing, which involves students' reflective thinking. Originality/value: It is hoped that the analysis can serve as reference for internship courses planning in the future.